Pathogenesis of the metabolic syndrome - Bergman, Richard (Henry Stewart Talks, 2007)
Metabolic syndrome and type 2 diabetes, Risk and effect of obesity, "Metabolic syndrome", Pathogenesis of the metabolic syndrome, Visceral and subcutaneous adiposity in the fat-fed dog model, "Overflow" hypothesis, Control diet and high fat diet, Visceral adiposity, Hepatic and peripheral insulin resistance, Distribution of insulin with obesity, Transendothelial insulin transport (TET), Hyperinsulinemia, Insulin resistance
Archived at 2025/05/28